Gebelere uygulanan İnsan Anti-D İmmünglobulin enjeksiyonu ağrısının azaltılmasında manuel basınç ve lokal soğuk sprey uygulamanın etkinliğinin değerlendirilmesi : randomize kontrollü çalışma - Coşkun, Ümmü Gülsüm (My University, 2024)
Amaç: Gebelere uygulanan İnsan Anti-D İmmünglobulin enjeksiyonuna bağlı gelişen ağrının azaltılmasında manuel basınç, lokal soğuk sprey uygulamanın ağrı şiddeti, hemodinamik parametreler ve memnuniyete etkisini belirlemek amacı ile gerçekleştirildi. Gereç ve Yöntem: Bu araştırma Randomize Kontrollü (Clinical Trials ID: NCT06231719) girişimsel bir araştırmadır. Çalışmanın evrenini Aralık 2023-Nisan 2024 tarihleri arasında İstanbul İl Sağlık Müdürlüğü’ne bağlı bir Şehir Hastanesinde Rh uyuşmazlığı sorunu olan gebeler oluşturdu. Örneklemi ise İnsan Anti-D İmmünglobulin Enjeksiyonu reçete edilen, araştırmaya dahil edilme kriterlerini karşılayan gebeler oluşturdu. Örnekleme her gruba [Manuel Basınç (MB), Lokal Soğuk Sprey (LSS), Kontrol Grubu (KG)] 43, toplamda 129 gebe alındı. Gebelere enjeksiyon öncesi Tanıtıcı Bilgi Formu ve Ağrı Korkusu Ölçeği III (AKÖIII) uygulandı. Enjeksiyon uygulamadan 5 dakika önce hemodinamik parametreleri (kan basıncı, nabız, solunum, oksijen saturasyonu) ölçüldü. Enjeksiyon öncesi KG gebelerine standart IM enjeksiyon prosedürü, MB grubuna manuel basınç, LSS grubuna 2 kez soğuk sprey sıkıldı. Enjeksiyon sonrasında ağrı şiddetlerini değerlendirmeleri için Görsel Kıyaslama Ölçeği (GKÖ) ve Enjeksiyon Memnuniyet Ölçeğini (EMÖ) işaretlemeleri istendi. Enjeksiyon uygulandıktan 5 dakika sonra tekrar hemodinamik ölçümleri alındı. Bulgular: Gebelerin yaş, fiziksel ve sosyodemografik özellikleri ile AKÖIII puan ortalamaları benzer bulundu (p>0.05). Enjeksiyon sonrası LSS ve MB grubundaki gebelerin ağrı puan ortalamaları KG’deki gebelere göre daha düşüktü ve aralarında fark istatistiksel olarak ileri derecede anlamlı bulundu (p<0.001). Ancak 3 grubun EMÖ puan ortalamaları benzerdi (p>0.05). Sonuç: Gebelere enjeksiyon öncesi uygulanan manuel basınç ve lokal soğuk spreyin enjeksiyon ağrısını azalttığı ancak enjeksiyon memnuniyetini etkilemediği belirlendi.

Objective: The aim of the study was to determine the effect of manual pressure, local cold spray administration on pain intensity, hemodynamic parameters and satisfaction in reducing pain due to Human Anti-D Immunoglobulin injection administered to pregnant women. Materials and Methods: This study is an interventional randomised controlled trial (Clinical Trials ID: NCT06231719). The population of the study consisted of pregnant women with Rh alloimmunization who were monitored in the pregnancy polyclinics of a City Hospital affiliated to Istanbul Provincial Health Directorate between December 2023 and April 2024. The sample consisted of pregnant women who were prescribed Human Anti-D Immunoglobulin injection due to Rh alloimmunization and met the inclusion criteria. The sample included 43 pregnant women in each group [Manual Pressure (MB), Local Cold Spray (LCS), Control Group (CG)], a total of 129 pregnant women. An Introductory Information Form and the Fear of Pain Scale III (FPSIII) were filled out before injection. Hemodynamic parameters (blood pressure, pulse, respiration, oxygen saturation) were taken 5 minutes before injection. Before the injection, standard IM injection procedure was applied to the CG, manual pressure was applied to the MB group and cold spray was applied twice to the LCS group. After the injection, they were asked to mark the Visual Analog Scale (VAS) and Injection Satisfaction Scale (ISS) to evaluate their pain intensity. Hemodynamic measurements were taken again 5 minutes after the injection. Results: The average age, physical and sociodemographic characteristics of the pregnant women, as well as their FPS-III mean scores, were found to be similar (p>0.05). The total pain scores of the pregnant women in the LCS and MP groups were lower than those in the CG and the difference between them was found to be highly statistically significant (p<0.001). However, the ISS mean scores of the three groups were similar (p>0.05). Conclusion: It was determined that the application of manual pressure and local cold spray before the injection reduced the injection pain in pregnant women but did not affect their satisfaction with the injection procedure.
Evaluation of the efficacy of manual pressure and local cold spray application in reducing pain caused by Human Anti-D Immunoglobulin injection in pregnant women : a randomized controlled stud
Keywords: Doğum hemşireliği; Enjeksiyon ağrısı; human anti-D immunoglobulin; Injection pain; insan anti-D immünglobulin; local cold sprey; lokal soğuk sprey; manual pressure; manuel basınç; Obstetric nursing; Rh alloimmunization; Rh uyuşmazlığı